INVESTIGATING FLUID PARAMETERS IN NANOFIBER BIOMATERIAL FABRICATION USING ELECTROSPINNING - Yusro, Muhammad; Martien, Ronnie (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2020)
Fabricating nanofiber biomaterial using electrospinning is difficult due to its bioactive characteristics. Even though electrospinning is mentioned as the most well-established approach to produce nanofiber, it is undeniable that fluid factors involved in determining the product result. In this research, three influenced factors including viscosity, conductivity, and surface tension are investigated in the system of Biomaterial Composite that contains mixed Chitosan-Pectin material blended to the Polyvinyl Alcohol (PVA). Various concentrations were made up to create an assorted liquid profile to some extent influencing fluid characteristic which affecting fabrication result. This research also analyzed the interaction between group materials using Fourier Transform Infra-Red (FTIR). Moreover, bead and spray phenomena which are commonly occurred in the process of fabrication are also deliberated correlating with fluid parameters. This experiment revealed that the range of the ability of the composite solution that can be fabricated was from 90/10 to 60/40 with the average diameter size for each composition are 90/10 = 155,39 ± 43,68 nm, 80/20 = 99,03± 26.01 nm, 70/30 = 111,387 ± 50,06 nm, and 60/40 = 107,06 ± 47,36 nm. Regarding fluid characteristics, the discrepancy related to the effect of viscosity to nanofiber size has occurred due to the nonuniform shape and type that affected the average size of the nanofiber. Meanwhile, the conductivity parameter found as the main reason related to the limited ability of the electrospinning process. Furthermore, the surface tension parameters noted as a factor that influencing droplet and beads formation.